An acoustic microprobe - LITNIEWSKI, Jerzy (Archives of Acoustics, 1988)
In the paper the structure of an acoustic microprobe has been presented of which the resolution does not depend on the receiving transducer dimensions. With this microprobe the acoustic pressure amplitude can be measured with the resolution below the wave length in liquid media and at the surface of solids, in the frequency range from 30 to 40 MHz. The method of finding the resolving power of the microprobe by measuring the response function for a point source has been described. Resolution of the microprobe has been estimated as better than 25 gm what is about 1/2 of the wave length in water and 1/7 of the longitudinal wave length in such materials as aluminium or glass. The directional response pattern which is necessary for taking measurements at the non-planar surfaces of solids, has been found. The possibility of applying the microprobe to measuring the pressure amplitude distribution at the surface of lenses used in acoustic microscopy has been demonstrated.